Structure-functional characterization of cytochrome P4502E1 (CYP2E1) - Danko, I.M.; Chaschin, N.A. (Біополімери і клітина, 2007)
This review summarizes data on expression level and localization, structure and functional properties of cytochrome P4502E1 (CYP2E1). Induction of CYP2E1 synthesis and activity by compounds with various chemical structures and under certain pathophysiological states is considered. Special emphasis is placed on CYP2E1 expression inhibitors. The latest data on CYP2E1 expression regulation and degradation mechanisms are analyze.